Advances in Antimicrobial Coatings - Rtimi, Sami (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is motivated by our passion to compile recent research on antimicrobial surfaces. We aimed to assemble research papers on the preparation of new materials, antimicrobial testing using different pathogens (bacteria, fungi, and viruses), and the relationship between the coating nanostructure and its reactivity towards the studied pathogen(s). We believe that a good antimicrobial coating should by characterized by (i) a fast activity towards the pathogen, (ii) sustainable activity based on the stability of the coating, and (iii) the lowest possible toxicity for humans and reduced risks for the environment. Striking a compromise between these different challenges is difficult and requires more research.